Essential business grammar and practice : elementary to pre-intermediate. - Duckworth, Michael, ....- (Oxford : University Press, 2006)
This new Elementary level provides clear explanations and examples of key grammar relevant to lower-level learners, with practice activities based on authentic contexts and opportunities for personalization in each unit. Key features > Clear, simple explanations of grammar points appropriate for lower-level learners. > Straightforward practice activities based on accuracy. > Authentic source material, providing contexts relevant to adult professional learners' needs. > Short end-of-unit sections allowing students to personalise key grammar. > Progress tests.
Keywords: Engels -- Zakenleven; Engelse spraakkunst